2013
DOI: 10.1016/j.jcmg.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

CRT Improves LV Filling Dynamics

Abstract: Echocardiographic particle imaging velocimetry allows blood flow visualization and characterization of diastolic vortex formation that may play a key role in filling efficiency. We hypothesized that abrupt withdrawal of cardiac resynchronization therapy (CRT) would alter the timing of left ventricular diastolic vortex formation and modify cardiac time intervals. In patients with heart failure (HF) who had chronically implanted CRT devices, the timing of the onset of the diastolic vortex (TDV) from mitral valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Shortening the filling period by programing long electrical AV delays increases the circulation and kinetic energy of the vortex and results in the vortex staying closer to the mitral valve [28]. When compared to baseline conduction, biventricular stimulation seems to improve organization of intraventricular flow, suggesting that intraventricular flow analysis is a useful tool to understand the effects of resynchronization on heart mechanics [30]. Remarkably, changes in electrical activation have been shown to modify the net orientation of the forces acting on blood inside the LV, which has been associated with improved long-term outcome in patients undergoing CRT [31].…”
Section: Introductionmentioning
confidence: 99%
“…Shortening the filling period by programing long electrical AV delays increases the circulation and kinetic energy of the vortex and results in the vortex staying closer to the mitral valve [28]. When compared to baseline conduction, biventricular stimulation seems to improve organization of intraventricular flow, suggesting that intraventricular flow analysis is a useful tool to understand the effects of resynchronization on heart mechanics [30]. Remarkably, changes in electrical activation have been shown to modify the net orientation of the forces acting on blood inside the LV, which has been associated with improved long-term outcome in patients undergoing CRT [31].…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated the value of systolic dyssyncronicity index, as assessed by 3D echocardiography, in correctly predicting CRT‐responders, while other parameters such as QRS duration were not predictive of either clinical or echocardiographic outcomes. Soliman et al., identified an SDI value >10% as highly predictive of positive outcome after CRT. In agreement with our data, Marsan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Also, in an elegant echo-PIV study in eleven heart failure patients with implanted CRT, Goliasch and co-workers showed that the onset of the LV filling vortex formation during early diastole was significantly delayed when the CRT was deactivated and was immediately reversed upon reactivation [ 11 ]. The authors stated that this delay was due to a disorganized LV inflow with reduced acceleration during early diastole caused by LV dyssynchrony.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of intracardiac blood flow demonstrates fundamental aspects of cardiac function in health and disease [ 8 11 ]. 4D flow cardiovascular magnetic resonance (CMR) is a versatile and promising method for the assessment of intracardiac flow [ 12 17 ].…”
Section: Introductionmentioning
confidence: 99%